The analysis of successfully applied techniques in part 1 in ju-jitsu fighting - Staller, M. (LASE Journal of Sport Science, 2013)
Empirical data of technical and tactical performance in ju-jitsu fighting (JJF) competitions are rare, making it hard to derive validated recommendations for JJF training. Therefore, the current study investigated successfully applied punching and kicking techniques, which were performed in JJF competition at a world-class level. For this purpose 399 techniques, which were applied at the 2010 World Championships and were awarded with points by the referees, were systematically analyzed. Results revealed that punches are more likely to score "ippon" than kicks. Furthermore, the straight punch with the backhand could be identified as the most successfully applied technique, which is most likely to score "ippon" as a single counter technique. Practical implications of the results for training and recommendations for tactics in competition are drawn. Therefore, it is suggested to focus on punches in order to score "ippon". Furthermore, a more defensive fighting style increases the likelihood to be awarded "ippon" for a straight punch with the back hand, being the most dominant technique in part 1. Together with the existing literature it is suggested to behave tactically flexible and not to behave too defensive in ju-jitsu fighting fights. Further studies have to incorporate more techniques of different competitions at a world-class level.